A Research Agenda for Border Studies - Scott, James Wesley, 1956- (Cheltenham, UK: Edward Elgar Publishing, 2020)
Elgar Research Agendas outline the future of research in a given area. Leading scholars are given the space to explore their subject in provocative ways, and map out the potential directions of travel. They are relevant but also visionary. The power of borders emerges not only from their institutional and legal nature but also from their symbolic and identity-forming significance. This innovative Research Agenda uncovers links between different levels of border-making processes, or bordering, from the political to the cognitive, and connects everyday processes and experiences of border-making to the wider social world. Grounded in their original research, contributors offer a variety of discussions on future directions for border studies, including two areas which may prove particularly fruitful; firstly, the question of the broader political salience of borders and secondly, the ways in which the border studies paradigm increasingly connects ontological and ethical questions to processes of border-making. Taken together, these address the question of how everyday bordering practices and discourses can be productively linked to different aspects of social relations. This timely book will be an invigorating read for those studying borders across a wide range of disciplines including human geography, political science, sociology, anthropology, history, international law as well as the humanities, notably art, media studies and philosophy. --
Includes bibliographical references and index.
Keywords: Boundaries -- Research; Informational works